l-Tryptophan improves the sperm quality of threatened Abant trout (Salmo abanticus) against glyphosate toxicity: impact on oxidative stress and DNA damage - Kocabas, Mehmet; Kocabas, Filiz Kutluyer; Erisir, Mine; Benzer, Fulya; Arslan, Halil Ozancan; Keles, Esin; Aksu, Onder (Taylor & Francis Inc, 2025)
The current study focused on the ameliorating impact of TRP (5 mM) on Salmo abanticus spermatozoa exposed to sub-lethal concentrations of GLY (2.5, 5, and 10 mg/L). Sperm quality parameters, oxidative stress indices, and DNA damage were analyzed in the post-exposure sperm. Our data reveal that GLY has an adverse effect on motility rate and duration, sperm kinetics parameters, antioxidant status and DNA damage, and triggers antioxidant defense mechanisms at the highest dose (10 mg/L) and it has insufficient therapeutic effect. Overall, GLY poses potential hazards to male reproductive cells and may adversely affect subsequent generations of natural populations.
Keywords: l-Tryptophan; glyphosate; spermatozoa; oxidative stress; Abant trout